Creativity and skills formation features creative thinking in preschool children through literary creation. - Anorboev, Akmal (Maktabgacha taʼlim jurnali, 2020)
Abstract: Research into the formation of creative thinking is based on works of foreign and domestic classics of pedagogy and psychology, pedagogical and psychological theories of the development of creative abilities personality. “Creativity in the narrow sense of the word is a divergent thinking, the hallmark of which is multidirectionality and variability of search for different, equally correct decisions regarding the same situation.